Microbially Enhanced Growth and Metal Capture by Ferromanganese Concretions in a Laboratory Experiment - Majamäki, Renata; Wasiljeff, Joonas; Purkamo, Lotta; Hultman, Jenni; Asmala, Eero; Yli‐Hemminki, Pirjo; Koho, Karoliina; Jørgensen, Kirsten S.; Kuva, Jukka; Virtasalo, Joonas J. (Wiley-Blackwell, 2025)
The growth and metal enrichment of ferromanganese minerals on the seafloor have intrigued many studies, yet the role of microbes in the process has remained elusive. Here, we assessed the microbial influence on the growth and trace metal accumulation and release of ferromanganese concretions from the Baltic Sea using 12-week microcosm incubation experiments. We studied three concretion morphotypes: Crust, discoidal, and spheroidal, with biotic and abiotic treatments. The concretion samples were collected into bottles containing artificial brackish seawater from the Gulf of Finland, incubated in in-situ simulating conditions, and sampled at the beginning and end of the experiment. Microscale X-ray-computed tomography confirmed the local growth of up to 10 μm thick patches on the concretion surface during the 12-week incubation period, corresponding to a growth rate of 0.04 mm/year. Scanning electron microscopy of glass slides in the microcosms revealed freshly precipitated cauliflower-like grains, typical of freshly formed Fe- and Mn-hydroxides. Decreased concentrations of dissolved trace metals (Mn, Fe Co, V, Ni, Zn, and Mo) in the incubation solutions indicated the accumulation of these elements into concretions in the biotic microcosms. In contrast, the dissolution of concretions was observed in abiotic microcosms, confirming that microbial activity enhanced the ferromanganese precipitation and the associated accumulation and release of P and trace metals into the ambient solution. The microbial contribution was confirmed by a strong decrease in headspace methane concentrations in biotic microcosms, further indicating the presence of active methanotrophs in the concretion communities.
Keywords: Baltic Sea; biomineralization; ferromanganese; metal enrichment; microbial activity